Cloning and genetic analysis of the Vibrio vulnificus fur gene and construction of a fur mutant by in vivo marker exchange. - Litwin, C M (1993)
Vibrio vulnificus infections have been associated with iron overload and preexisting liver disease. Iron may play a major role in the pathogenesis of V. vulnificus infections. Many virulence genes, as well as genes involved in the transport of iron by bacteria, are regulated by iron, with increased expression under low-iron conditions. In Escherichia coli and Vibrio cholerae, transcriptional regulation by iron depends on the fur gene. We utilized Southern hybridization under low- and high-stringency conditions with both E. coli and V. cholerae fur gene probes to demonstrate that there are fur-homologous sequences in the DNAs of V. vulnificus, Vibrio fischeri, and Aeromonas sp. but not in the DNAs of the other bacterial species tested. We developed a restriction map and cloned the fur-homologous sequence from V. vulnificus. The hybridizing clone of V. vulnificus chromosomal DNA complemented a V. cholerae fur mutant. DNA sequence analysis confirmed the presence of a 149-amino-acid open reading frame that was 77% homologous to E. coli Fur and 93% homologous to V. cholerae Fur. Primer extension localized a single promoter for the V. vulnificus fur gene. Northern (RNA) blot analysis and beta-galactosidase assays of an operon fusion to lacZ suggested that there was not significant regulation of transcription of V. vulnificus fur by iron or the E. coli Fur protein. We used marker exchange to construct a V. vulnificus fur deletion mutant and confirmed its phenotype by observing overexpression of iron-regulated outer membrane proteins on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The fur deletion mutant of V. vulnificus will be helpful in future studies of the role of iron in V. vulnificus pathogenesis.